Projection from the Anterior Cingulate Cortex to the Lateral Part of Mediodorsal Thalamus Modulates Vicarious Freezing Behavior - Zheng, Chaowen (Neurosci Bull, 2019)
Emotional contagion, a primary form of empathy, is present in rodents. Among emotional contagion behaviors, social transmission of fear is the most studied. Here, we modified a paradigm used in previous studies to more robustly assess the social transmission of fear in rats that experienced foot-shock. We used resting-state functional magnetic resonance imaging to show that foot-shock experience enhances the regional connectivity of the anterior cingulate cortex (ACC). We found that lesioning the ACC specifically attenuated the vicarious freezing behavior of foot-shock-experienced observer rats. Furthermore, ablation of projections from the ACC to the mediodorsal thalamus (MDL) bilaterally delayed the vicarious freezing responses, and activation of these projections decreased the vicarious freezing responses. Overall, our results demonstrate that, in rats, the ACC modulates vicarious freezing behavior via a projection to the MDL and provide clues to understanding the mechanisms underlying empathic behavior in humans.